Penyengatan Meningeal Sisterna Basalis Meningitis TB pada Computed Tomography Scanning: Sebuah Ulasan Bergambar - Anastasia Tjan; Made Widhi Asih; Elysanti Dwi Martadiani (Universitas Wijaya Kusuma Surabaya, 2019)
Tuberculosis (TB) is one of the major worldwide threat and global burden in Indonesia. CNS tuberculosis is the most severe form of TB infection. CT evaluation on diagnosing tuberculosis meningitis (TBM) with triad of hydrocephalus, basal meningeal enhancement and infarction was reported to be sensitive. PCR cerebrospinal fluid (CSF) is known to be specific, however negative results have been reported due to presence of PCR’s inhibitors, poor lysis of mycobacteria, and the uneven distribution in specimens. CT Scan plays the vital role in diagnosing TBM patient with the presence of TBM CT triad, especially basal cistern enhancement (BME) which is the specific enhancement pattern in MTB patient. There are 9 must know BME pattern, such as contrast filling the cistern, double and triple line, linear enhancement at MCA cistern, Y sign, posterior infundibular recess enhancement, ill defined border, join the dots sign, nodular enhancement, and asymmetry off all pattern. Familiarizing BME criteria is essential to provide confident diagnosis and reduce morbidity and mortality